STRATEGI BERTAHAN HIDUP PETANI SAYUR DI KELURAHAN KAMPUNG MANGGIS KECAMATAN PADANG PANJANG BARAT KOTA PADANG PANJANG - Rony Verdianto; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
As a vegetable farmer who has imited land, the farmers in the Sub-district Kampung Manggis have their own difficulties in fulfilling their family’s economic needs. This study was conducted in the Sub-district of Manggis Village, West Padang Panjang District, Padang Panjang City. The goal is to find out the vegetable farmer’s survival strategy. Sample writing techniques using purposive sampling in determining the informant. The research methods used are qualitative descriptive research methods.Purposive sampling is the taking of the subject based on certain criteria and the subject has problems in farming and economics. The theory used is the survival theory of Pierre Bordieu, which is a long-term strategy including biological investment strategies and symbolic investment strategies,as well as short-term strategies, namely successive strategies, educational strategies amd economic investment strategies. The result of the writing explains. (1) The Biological Investment Strategy is not implemented by vegetable farmers in the village of Manggis Village. (2) Successive Strategy are implemented by reducing the expenditure money. (3) Educational Strategies are carried out by following a farmer groups.(4) Economic Investment Strategy is carried out by increasing capital by borrowing money from relatives, and increasing social capital. (5) Simbolic Investmen Strategy carried out by improving children’s education up to university. Keywords: Survial Strategy, Vegetable Farmers.